Towards sustainability and beyond with Ocean Health Science - S. Plön; K. Andra; L.-M. Auditore; C. Gegout; P. Hale; O. Hampe; M. Ramilo-Henry; P. Burkhardt-Holm; A. M. Jaigirdar; L. Klein; M. K. Maewashe; J. Müssig; et al. (npj Biodiversity)
Abstract Marine mammals as indicators of Ocean Health provide a powerful narrative for inter-, multi- and transdisciplinary research. Collaborating researchers from the global north and south from various disciplines define and position OceanHealth as a transdisciplinary discourse among existing disciplines and propose a new solution-focused knowledge field, Ocean Health Science. This systemic approach advocates transformative thinking with the goal to heal and nurture our global Ocean and the potential for big science, encouraging the global community to take a shared stewardship responsibility.